Study of the innovation management process in the development of a discontinuous product case: Motorola RAZR V3 - Santos Junior, José Maria Ewerton dos (2010)
This study will collaborate by bringing some detailed analysis and findings on a special case study of a discontinuous product development process, trying to answer how the discontinuous product development process takes place and the main factors that influence this process. Additionally, it tried to explore some explanations for the difficulties generally faced by the companies to sustain innovation. The case is about the Motorola cell phone RAZR V3, launched in 2004. RAZR V3 was noted by industry experts as game-changing feat of design and engineering, selling more than 110 million units by end of 2008 and recognized as one of the fastest selling products in the industry. The study uses a single case methodology, which is appropriate given the access to a phenomenon that happened inside corporate dominium and it is not easily accessed for academic studies, besides being a rare case of success in the cellular phone industry. In order to magnify the understanding of the phenomenon, the exploration was extended to contrast the RAZR development process and the standard product development process in Motorola. Additionally, it was integrated a longitudinal reflection of the company product development evolution until the next breakthrough product hitting the cellular phone industry. The result of the analysis shows that discontinuous products do not fit well traditional product development process (in this case, stage-gate). This result reinforces the results obtained on previous studies of discontinuous product development conducted by other authors. Therefore, it is clear that the dynamics of discontinuous product development are different from the continuous product development, requiring different treatment to succeed. Moreover, this study highlighted the importance of the management influence in all the phases of the process as one of the most important factors, suggesting a key component to be carefully observed in future researches. Some other findings of the study that were considered very important for a discontinuous product development process: have champions (who believe and protect the project) and not only one champion; create a right atmosphere to make flow the creative process; question paradigms to create discontinuous products; simple guiding light to focus the team; company culture that accepts and knows how to deal with risks; and undoubtedly, have a company strategy that understands the different dynamics of continuous and discontinuous product development processes and treat them accordingly.